ANALYSIS OF SECONDARY METABOLITES, ANTIBACTERIAL ACTIVITY AND COMPOUND COMPOSITION IN THE SEA CUCUMBER Bohadschia sp. EXTRACT - Abdullah Rasyid (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
Bohadschia sp. is one of the sea cucumber species that has potential to be developed as a source of antibacterial from the sea. Samples of sea cucumber Bohadschia sp. used in this study collected from the Ratai bay waters, Lampung. This study aims to determine the type of secondary metabolites, antibacterial activity and compound composition analysis containing in the sea cucumber extract. Identification of secondary metabolites by observation of color reactions, precipitation and foam. The method used to antibacterial activity test was the agar diffusion method, while identification of the composition of compounds performed with Gas Chromatogaphy-Mass Spectroscopy (GC-MS) method.Top of FormThe results showed that the type of secondary metabolites contained in the extract of sea cucumber Bohadschia sp. were steroids and saponins. The extract of sea cucumber Bohadschia sp. showed antibacterial activity against Bacillus subtilis and Vibrio eltor. Results of GC-MS were 12 compounds and have a similarity index same or more than 90%. All compounds consist of organosilicon cyclic, fatty acid, steroid, cyclo alkene and alkena. The compound with biggest abundance was cholest-5-en-3-yl nonanoate (4.89%) and retention time was 37.370 minutes.